Psychological distress as a mediator between workplace violence and turnover intention with caring for patients with COVID-19 - Nam, Sujin; Wong, Janet Yuen Ha; Wang, Tingxuan; An, Bomi; Fong, Daniel Yee Tak (Frontiers in Psychology, 2024)
The Coronavirus Disease 2019 (COVID-19) outbreak exacerbated workplace violence and turnover intention among nurses, particularly affecting greater levels of psychological distress. This study aimed to examine psychological distress as a mediator of the relationship between workplace violence and turnover intention among clinical nurses, and to investigate whether caring for patients with COVID-19 moderates this relationship through the lens of the affective events theory. We conducted an online survey of 325 Korean registered nurses (mean age = 30.75; female = 92.6%) who work in clinical settings between August and October 2021 using the convenience sampling method. Psychological distress was measured using the 21-item Depression Anxiety Stress Scale and workplace violence using one dichotomous item adopted from the Workplace violence questionnaire. We measured turnover intention using the six-item Anticipated Turnover Scale. Caring for patients with COVID-19 was determined using one dichotomous item. The research hypotheses assume that the relationship between workplace violence and turnover intention could be mediated by psychological distress and moderated by caring for patients with COVID-19 among Korean nurses. We performed a moderated mediation analysis with workplace violence as the independent variable, turnover intention as the dependent variable, psychological distress as a potential mediator, and caring for patients with COVID-19 as a potential moderator. The analysis revealed that nurses’ psychological distress among 308 nurses had a statistically significant mediating effect on the relationship between workplace violence and turnover intention. Furthermore, caring for patients with COVID-19 had a significant further moderating effect on this relationship. These findings highlight the need for psychological support services for clinical nurses at institutional and organizational levels amidst the ongoing COVID-19 pandemic. It is hoped that these findings can contribute to the development of tailored interventions for nurses caring for patients with COVID-19 to attenuate their psychological distress in a timely and effective manner.